An Exercise Programme for Smoking Cessation: Perceptions of the Fit2quit Trial Intervention. (4th August 2014) - Roberts, Vaughan; Dale, Leila Pfaeffli; Dorey, Enid; Bullen, Christopher; Maddison, Ralph
Abstract : Introduction: Few trials of exercise interventions for smoking cessation have included a qualitative evaluation of the intervention from the participants' perspective. Aims: To determine the perceptions of participants who received a 6-month telephone counselling exercise intervention to aid smoking cessation. Methods: Participants in the Fit2Quit study intervention group were asked to take part in a semi-structured phone interview. All interviews were digitally recorded and transcribed verbatim, and a general inductive approach to data analysis was followed. Results/Findings: Twenty participants from the intervention group completed an interview. The following themes emerged from the analyses: (1) The support people were genuinely interested in what I was achieving, (2) new awareness, new attitude, new lifestyle: I could see the benefits, (3) lack of time, willpower and money stopped me from changing and (4) I would have preferred a "more hands on" approach: Recommendations for future programmes. Conclusions: A telephone counselling intervention to enhance exercise for smoking cessation was well received. Aspects of the intervention, particularly the provision of support and encouragement from the participant support person, were beneficial. Suggested improvements were greater tailoring of the call schedule, greater face-to-face contact and provision of a buddy system or support group. Such improvements may increase adherence and, therefore, effectiveness of exercise interventions for smoking cessation.